Measuring, Modeling, and Forecasting the Mental Wealth of Nations - Occhipinti, Jo-An; Buchanan, John; Skinner, Adam; Song, Yun Ju C.; Tran, Kristen; Rosenberg, Sebastian; Fels, Allan; Doraiswamy, P. Murali; Meier, Petra; Prodan, Ante; Hickie, Ian B. (Frontiers in Public Health, 2022)
The COVID-19 pandemic has exposed the deep links and fragility of economic, health and social systems. Discussions of reconstruction include renewed interest moving beyond GDP and recognising ‘human capital’, ‘brain capital’, ‘mental capital’, and ‘wellbeing’ as assets fundamental to economic reimagining, productivity, and prosperity. This paper describes how the conceptualisation of Mental Wealth provides an important framing for measuring and shaping social and economic renewal to underpin healthy, productive, resilient, and thriving communities. We propose a transdisciplinary application of systems modelling to forecast a nation’s Mental Wealth and understand the extent to which policy-mediated changes in economic, social, and health sectors could enhance collective mental health and wellbeing, social cohesion, and national prosperity. Specifically, simulation will allow comparison of the projected impacts of a range of cross-sector strategies (education sector, mental health system, labour market, and macroeconomic reforms) on GDP and national Mental Wealth and provide decision support capability for future investments and actions to foster Mental Wealth. Finally, this paper introduces the Mental Wealth Initiative that is harnessing complex systems science to examine the interrelationships between social, commercial, and structural determinants of mental health and wellbeing, and working to empirically challenge the notion that fostering universal social prosperity is at odds with economic and commercial interests.